Trabalho com famílias na educação infantil: concepções e práticas - Lopes, Claudia Cristina Garcia Piffer [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Este texto trata de um estudo desenvolvido junto ao curso de Mestrado do Programa de Pós- Graduação em Educação da Unesp de Presidente Prudente – SP e se vincula à Linha de Pesquisa Práticas Educativas e Formação de Professores. O objeto de pesquisa consistiu no estudo das relações entre instituições de Educação Infantil e famílias. O problema referiu-se ao quadro de desencontro geralmente presente entre ambas. A pesquisa teve como objetivo geral a investigação das relações que se estabelecem entre instituições de Educação Infantil e famílias, bem como as concepções que as determinam, visando contribuir com a reflexão sobre o assunto. Foram estabelecidos como objetivos específicos a identificação e análise das propostas de trabalhos com famílias existentes nas unidades de Educação Infantil que atendem exclusivamente crianças na faixa etária compreendida entre zero a seis anos, mantidas pela Prefeitura Municipal de Presidente Prudente, buscando verificar quais concepções (de criança, família, Educação Infantil e papel dos profissionais) têm como base. Outro objetivo específico foi a contribuição para o direcionamento de possíveis ações de formação destinadas aos profissionais da Educação Infantil, a partir das reflexões suscitadas pelos resultados da pesquisa...

This text refers to a Master's degree study concerning the Program of Postgraduation in Education of Unesp of Presidente Prudente – SP in the field of Education Practices and Teacher Formation. The object of the research was the study of the relations between the Children Education Institutions and Families. The problem referred to the lack of connection between both. The research had as its general objective the investigation of the relations between Children Education institutions and families, as well as the conceptions that determine them, in order to contribute with the reflection about the subject. The identification and analysis of the actions proposals with families in the units of Children Education exclusively for children from zero to six years old kept by Presidente Prudente municipality in order to detect which conceptions (of child, family, Children Education and professional’s roles) that are their basis were the specific goals established. Other objective concerned the contribution for other possible formative actions aimed at the Children Education professionals’ formation, based on the reflections aroused by the research results and also focusing on the importance of the professionals that deal directly with the child role in the interactions between the families and Children Education institutions. The analysis was theoretically fundamented in the approaches that consider the inter-relations among child, family and Children Education and in references that understand the child as subject of rights...(Complete abstract, click electronic access below)
Keywords: Educação; Família; Crianças; Educação de crianças; Educação pre-escolar; Family; Children; Children Education